Prognostic value of postoperative decrease of albumin (ΔAlb) in combination with GLIM-defined malnutrition for the prediction of postoperative outcomes in rectal cancer patients with normal preoperative albumin levels - Zhou, Chong-Jun; Ling, Ke-Yu; Fang, Jun; Ye, Meng-Fan; Liu, Meng-Li; Chen, Jia-Can; Zheng, Chen-Guo; Li, Shao-Tang (Frontiers in Nutrition, 2025)
ObjectiveThis study aims to explore the prognostic value of ΔAlb in combination with malnutrition for postoperative outcomes in rectal cancer patients with normal preoperative albumin levels.MethodsWe conducted a retrospective study of patients undergoing proctectomy for rectal cancer at our department between January 2013 and April 2019. Malnutrition was defined according to the Global Leadership Initiative on Malnutrition (GLIM) criteria. A receiver operating characteristic curve analysis was used to determine the cut-off values for ΔAlb. Univariate and multivariate analyses evaluating the risk factors for postoperative complications and ΔAlb were performed.ResultsA total of 526 patients were enrolled in this study. ∆Alb was significantly associated with postoperative complications in patients with normal preoperative albumin levels (AUC = 0.651, p < 0.001), but was not in patients with hypoalbuminemia (p = 0.808). The optimal cut-off value was established at 16%. ∆ALB ≥ 16% and malnutrition were both independent risk factors for postoperative complications with an odds ratio (OR) of 2.179 and 1.730, respectively. When combined then together, the OR would reach to 3.779. On the other hand, low muscle mass (OR = 2.058, p < 0.001), tumor location in the lower third (OR = 2.909, p < 0.001), and surgical duration ≥ 180 min (OR = 1.659, p = 0.01) were identified as independent risk factors associated with ∆ALB.ConclusionΔAlb in combination with GLIM-defined malnutrition would enhance the predictive value for postoperative outcomes in rectal cancer patients with normal preoperative albumin levels, and it is necessary to conduct a nutritional assessment for then.